Removal of Patent Blue (V) Dye Using Indian Bael Shell Biochar: Characterization, Application and Kinetic Studies - Kangkan Roy; Kapil Mohan Verma; Kumar Vikrant; Mandavi Goswam; Ravi Kumar Sonwan; Birendra Nath Ra; Kowsalya Vellingiri; Ki-Hyun Kim; Balendu Shekher Gir; Ram Sharan Singh (MDPI AG, 2018)
The prospective utilization of bael shell (Aegle marmelos) as an agro-waste for the production of biochar was investigated along with its characterization and application for the abatement of hazardous aqueous Patent Blue (PB) dye solution. The sorptive removal of PB on bael shell biochar (BSB) was investigated under the following operational conditions: (pH, 2.7–10.4; biochar dosage, 2–12 g/L; and contact time, 0–60 min). The removal efficiency of PB by BSB in a batch adsorption experiment was 74% (pH 2.7 and 30 ± 5 ◦C). In addition, a clear relationship between the adsorption and pH of the solution was noticed and the proposed material recorded a maximum sorption capacity of 3.7 mg/g at a pH of 2.7. The adsorption of PB onto BSB was best explained by the pseudo-second order kinetic model (R2 = 0.972), thereby asserting the predominant role of chemisorption. The active role of multiple surface-active functionalities present on BSB during PB sorption was elucidated with the help of Freundlich isotherm (R2 = 0.968). Further, an adsorption mechanism was proposed by utilizing Fourier transform infrared spectroscopy (FTIR).
Keywords: adsorption; biochar; dye; kinetics; pollution control; wastewater treatment